Factors Affecting Research and the Treatment of Stroke in Women - Cunningham, Muriel (MD Conference Express, 2015)
Stroke is now the third-leading cause of death in women in the United States, and women tend to have worse poststroke outcomes. However, women tend to be underrepresented in clinical trials, and treatment is often suboptimal. Ways to narrow the sex treatment gap in stroke are reviewed.